Empowerment of Women Former Migrant Workers Through Community-Based Education: a Case Study of The Community of Desa Peduli Buruh Migran (DESBUMI) - Wafiroh, Nurotul; Septiarti, Serafin Wisni (Universitas Andalas, 2024)
This research explores the empowerment process for women former migrant workers through community-based education in the Desa Peduli Buruh Migran (DESBUMI) community in Jember Regency, Indonesia. It aims to examine community-based empowerment concepts and strategies to inform policies supporting women former migrant workers. Using a qualitative case study approach, data were gathered through observations, in-depth interviews, and documentation, followed by analysis through data reduction, presentation, and verification. The findings outline three empowerment stages: awareness, capacity building, and empowerment. In capacity building, an experiential learning cycle is used, tailored to the potential and needs of these women. Community interactions foster collective learning and mutual support, enhancing knowledge, skills, participation, and economic independence among former migrant workers. Additionally, the DESBUMI community provides a strategic platform for promoting local economic development. The research concludes that community-based education effectively strengthens both individual capacity and social networks, suggesting this model as a viable framework for empowering women in similar migrant worker communities across Indonesia.